Answers

2014-04-23T07:49:31+05:30
1/(a+1)+1/(b+1)+1/(c+1)
=1/(log base
x(yz) +1) + 1/( log base y(zx) +1 ) +1/(log base z(xy) +1)
=(log x/ log y+ log z + log x) + (log y/ log z + log x +log y ) + (log z / log x +log y + log z)
=logx +log y + log z / log x +log y +log z
=1
hence proved

1 5 1
thank you so much ^_^
u r always welcome dear :)
2014-04-23T12:04:29+05:30
1/(a+1)+1/(b+1)+1/(c+1)
=1/(log base 
x(yz) +1) + 1/( log base y(zx) +1 ) +1/(log base z(xy) +1)
=(log x/ log y+ log z + log x) + (log y/ log z + log x +log y ) + (log z / log x +log y + log z)
=logx +log y + log z / log x +log y +log z
=1
1 5 1